Om Prakash Sharma, MD, FRCP, FCCP - 4 July 1936 – 19 August 2012. Internationally acclaimed specialist in sarcoidosis - Baughman, R. P.; Drent, M.; Costabel, U. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Internationally acclaimed specialist in sarcoidosis